Covert marketing in films and series - Dimitrijević Ljiljana; Gojković Marija; Kolar Janez (Trendovi u Poslovanju)
Looking at the media, especially television, it is noticeable that marketing and advertising occupy an important segment. Organizations realize the importance of media advertising in order to promote their products and services. And while we are watching a movie or a favorite series, the advertising block and commercials do not bother us at all, and we use that time for other things. Although advertising represents an important segment of marketing, here we see its shortcomings. Modern business gives increasing commercial importance to covert marketing in films and series, and it is becoming an influential form of advertising. Practice records a large number of examples of successful applications of covert marketing (product placement). On the other hand, it is noticeable that covert marketing completely holds the attention of viewers or consumers. Its influence is growing, and through advertising through celebrities, who immediately draw attention to a certain brand or service, its attractiveness is growing. The main purpose of covert advertising is for the manufacturer to put their products and services in the real life context. The viewer identifies with the characters from the film or series, whose actions remind them of their life situations or what they aspire to, thus avoiding promotion through classic advertising blocks or space provided for advertisements, and the believability of the message is greatly increased.